2020
DOI: 10.1038/s41598-020-63301-3
|View full text |Cite
|
Sign up to set email alerts
|

Sciadonic acid derived from pine nuts as a food component to reduce plasma triglycerides by inhibiting the rat hepatic Δ9-desaturase

Abstract: Sciadonic acid (Scia) is a Δ5-olefinic fatty acid that is particularly abundant in edible pine seeds and that exhibits an unusual polymethylene-interrupted structure. Earlier studies suggested that Scia inhibited the in vitro expression and activity of the Stearoyl-CoA Desaturase 1 (SCD1), the hepatic Δ9-desaturase involved in the formation of mono-unsaturated fatty acids. To confirm this hypothesis, rats were given 10% Scia in diets balanced out with n-6 and n-3 fatty acids. In those animals receiving the Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Among the identified fatty acids, twelve are non-methylene-interrupted fatty acids including sciadonic acid (FA 20:3 n −6,9,15 at 47 ± 8 nmol mL −1 ) and keteleeronic acid (FA 20:2 n −9,15 at 2.4 ± 0.4 nmol mL −1 ). Polyunsaturated fatty acids that exhibit a pattern of unsaturation other than the canonical methylene-interrupted or conjugated sequences of double bonds have not previously been reported in human plasma but have been observed in other biological systems including pine nuts 56 , sea urchins 18 , mangos 57 , marine food webs 58 , dairy 59 , seed oils 22 as well as human breast milk 60 . Prior identification of non-methylene-interrupted fatty acids in foodstuffs may point to these being present in reference plasma as a result of dietary intake.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified fatty acids, twelve are non-methylene-interrupted fatty acids including sciadonic acid (FA 20:3 n −6,9,15 at 47 ± 8 nmol mL −1 ) and keteleeronic acid (FA 20:2 n −9,15 at 2.4 ± 0.4 nmol mL −1 ). Polyunsaturated fatty acids that exhibit a pattern of unsaturation other than the canonical methylene-interrupted or conjugated sequences of double bonds have not previously been reported in human plasma but have been observed in other biological systems including pine nuts 56 , sea urchins 18 , mangos 57 , marine food webs 58 , dairy 59 , seed oils 22 as well as human breast milk 60 . Prior identification of non-methylene-interrupted fatty acids in foodstuffs may point to these being present in reference plasma as a result of dietary intake.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified fatty acids, twelve are non-methylene interrupted fatty acids including sciadonic acid (FA 20:3 n -6,9,15 at 47 ± 8 nmol mL -1 ) and keteleeronic acid (FA 20:2 n -9,15 at 2.4 ± 0.4 nmol mL -1 ). Polyunsaturated fatty acids that exhibit a pattern of unsaturation other than the canonical methylene-interrupted or conjugated sequences of double bonds have not previously been reported in human plasma but have been observed in other biological systems including pine nuts, 45 sea urchins, 14 mangos, 46 marine food webs, 47 dairy 48 as well as human breast milk. 49 Prior identification of non-methylene interrupted fatty acids in foodstuffs may point to these being present in reference plasma as a result of dietary intake.…”
Section: Resultsmentioning
confidence: 98%
“…The anti-inflammatory and antioxidant effects of sciadonic acid, inhibiting the activity of phosphodiesterase and lipoxygenase-5, have been clearly demonstrated [ 144 ]. An in vivo study confirms that sciadonic acid markedly inhibits expression and activity of stearoyl-CoA desaturase 1, the hepatic Δ9-desaturase involved in the formation of MUFAs, which demonstrate promising effects on hyper-triglyceridemic models [ 145 ]. It has been shown that sciadonic acid can modify lipid metabolism in rats: when rats were fed sciadonic acid, the serum and liver triacylglycerol levels decreased [ 146 ].…”
Section: Echinoderm Fatty Acids As Bioactive Compoundsmentioning
confidence: 99%